Banco de pruebas de conductividad térmica en metales a la resistencia de contacto (2023)
Various types of laboratory experiments, integration of sensor-based technology for science learning is required to improve the quality of science education, especially to improve the quality of physical measurement. The use of sensor technology integrated with Arduino TM programming can handle the problem of real-time data recording. A conventional time-dependent physics experiment conducted in schools, students commonly enter data manually with the help of a stopwatch. However, conduction heat transfer phenomena cannot be explored unless one has the device to identify the timedependent heat changes during the investigation. Thus, a novel educational laboratory kit that investigates heat transfer is proposed. The time-dependent measurement employs an Arduino microcontroller based on temperature sensors